2015
DOI: 10.1093/mnras/stv2401
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared observations of PSR J1357−6429

Abstract: PSR J1357−6429 is a young radio pulsar that was detected in X-rays and γ-rays. We present the high spatial resolution near-infrared imaging of the pulsar field in J, H and K s bands obtained with the VLT/NaCo using the Adaptive Optic system. We found a faint source at the most precise pulsar radio position which we propose as the pulsar near-infrared counterpart candidate. It is confidently detected in the J and K s bands, with J = 23.51±0.24 and K s = 21.82±0.25. There is a hint of the source in the H band wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
5
4
0
Order By: Relevance
“…The power-law slope inferred for the DSO, see Eq. (1), is qualitatively consistent with the observations of neutron stars in near-infrared bands (Mignani et al 2012;Zharikov et al 2013;Zyuzin et al 2016), however, it appears to be steeper than for observed pulsars (Mignani et al 2012), which have the mean spectral index α ≈ 0.7.…”
Section: Possible Non-thermal Origin Of the Sed: Nir-"excess"supporting
confidence: 88%
See 1 more Smart Citation
“…The power-law slope inferred for the DSO, see Eq. (1), is qualitatively consistent with the observations of neutron stars in near-infrared bands (Mignani et al 2012;Zharikov et al 2013;Zyuzin et al 2016), however, it appears to be steeper than for observed pulsars (Mignani et al 2012), which have the mean spectral index α ≈ 0.7.…”
Section: Possible Non-thermal Origin Of the Sed: Nir-"excess"supporting
confidence: 88%
“…The qualitative behaviour of the continuum radiation of the DSO is similar to the SED of few young pulsars detected in NIR domains (Mignani et al 2012;Zharikov et al 2013;Zyuzin et al 2016) that are dominated by magnetospheric synchrotron radiation. Moreover, they exhibit a significant linear polarized emission with the polarization degree of a few 10% (Zajczyk et al 2012).…”
Section: Summary Of Observational Constraintssupporting
confidence: 70%
“…Furthermore, candidate counterparts have been found for PSR J0205+6449 (Moran et al 2013) and PSR J1357−6429 (Zyuzin et al 2016). Here, we found a candidate counterpart to another γ-ray pulsar, PSR J1741−2054.…”
Section: Discussionsupporting
confidence: 57%
“…PSR J1741−2054 would then be the third γ-ray pulsar discovered by Fermi for which a candidate optical/ infrared counterpart has been found, after PSR J0205+6449 (Moran et al 2013) and PSR J1357−6429 (Zyuzin et al 2016). Multi-epoch optical observations will allow us to measure the proper motion of the PSR J1741−2054 candidate counterpart and confirm the optical identification, whereas multi-band photometry will be needed to determine the pulsar spectrum in the optical.…”
Section: Discussionmentioning
confidence: 99%
“…Another handful of γ-ray pulsars have been observed after their discovery by Fermi, but not detected yet, with 10mclass telescopes: PSR J1357−6429 (Mignani et al 2011), PSR J1028−5819 (Mignani et al 2012), PSR J1048−5832 (Razzano et al 2013;Danilenko et al 2013), PSR J0007+7303 , PSR J0357+3205 (De Luca et al 2011;Kirichenko et al 2014), and PSR J2021+3651 (Kirichenko et al 2015). Recently, PSR J1357−6429 might have been identified in the near infrared (Zyuzin et al 2016).…”
Section: Introductionmentioning
confidence: 99%